Global Value Chain Participation and Industrial Upgrading: Evidence from Cross-Country Trade Integration Indicators - Angela Vitaloka; Jessica Lianita Agnelleide Loo (Cv. Data Sinergi Digital, 2025)
This study examines the relationship between global value chain (GVC) participation and industrial upgrading using a cross-country panel dataset of trade integration indicators covering 65 economies from 2005 to 2022. Drawing upon the OECD Trade in Value Added (TiVA) database and the World Bank's GVC indicators, the analysis decomposes GVC participation into forward and backward linkages and evaluates their distinct effects on industrial upgrading, measured by the share of medium-high and high-technology manufacturing in total value added. Employing a two-step system Generalized Method of Moments (GMM) estimator to address endogeneity, the findings reveal that both forward and backward GVC participation exert a statistically significant and positive effect on industrial upgrading, although the magnitude and channels differ substantially. Forward participation, reflecting a country's upstream positioning through the export of domestically produced intermediates, demonstrates a stronger upgrading effect (β = 0.438, p < 0.01) compared to backward participation (β = 0.267, p < 0.05). Further analysis shows that institutional quality, human capital, and foreign direct investment inflows moderate these relationships. The results are robust to alternative specifications and subsample analyses across income groups. This research contributes to the literature by providing novel empirical evidence on the nonlinear and heterogeneous nature of GVC-upgrading linkages, offering policy implications for developing economies seeking to leverage trade integration for structural transformation.